2017
DOI: 10.1093/aje/kwx164
|View full text |Cite
|
Sign up to set email alerts
|

Transportability of Trial Results Using Inverse Odds of Sampling Weights

Abstract: Increasingly, the statistical and epidemiologic literature is focusing beyond issues of internal validity and turning its attention to questions of external validity. Here, we discuss some of the challenges of transporting a causal effect from a randomized trial to a specific target population. We present an inverse odds weighting approach that can easily operationalize transportability. We derive these weights in closed form and illustrate their use with a simple numerical example. We discuss how the conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
279
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(280 citation statements)
references
References 16 publications
0
279
0
1
Order By: Relevance
“…Variables meeting this criterion were further assessed using interaction analyses with additional adjustment for potential confounders of their association with adenoma outcomes as well as using standardization methods (see below) to compare results across the two studies. To standardize the participant population in the CPPS or the VCPPS trial to the distribution of observed effect measure modifier in the other trial, we used inverse odds of sampling weights . Briefly, inverse odds of sampling weights use a form of model‐based standardization to transport the effects of an intervention in a given study population (in this case, the effects of calcium supplementation on adenoma risk in one of the two trials) to another target population (here, the other trial).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables meeting this criterion were further assessed using interaction analyses with additional adjustment for potential confounders of their association with adenoma outcomes as well as using standardization methods (see below) to compare results across the two studies. To standardize the participant population in the CPPS or the VCPPS trial to the distribution of observed effect measure modifier in the other trial, we used inverse odds of sampling weights . Briefly, inverse odds of sampling weights use a form of model‐based standardization to transport the effects of an intervention in a given study population (in this case, the effects of calcium supplementation on adenoma risk in one of the two trials) to another target population (here, the other trial).…”
Section: Methodsmentioning
confidence: 99%
“…To standardize the participant population in the CPPS or the VCPPS trial to the distribution of observed effect measure modifier in the other trial, we used inverse odds of sampling weights. 11 Briefly, inverse odds of sampling weights use a form of model-based standardization 12 to transport the effects of an intervention in a given study population (in this case, the effects of calcium supplementation on adenoma risk in one of the two trials) to another target population (here, the other trial). These methods have been applied to a variety of randomized clinical trials when seeking to generalize or transport treatment effects to other target populations of interest.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We use the term generalizability when the target population coincides or is a subset of the trial‐eligible population and transportability when the target population includes at least some individuals who are not trial‐eligible (and who, by definition, cannot be trial participants; others have proposed different definitions). In generalizability analyses, the target population often has a different distribution of effect modifiers compared with the participant population, even though both populations meet the trial eligibility criteria.…”
Section: Extending Trial Findings To a Target Populationmentioning
confidence: 99%
“…This tutorial builds on a growing literature to show that, instead of relying exclusively on informal assessments, we can use formal statistical methods to extend causal inferences from trial participants to a new target population. We focus on the common setting in which individual‐level data on time‐fixed treatments, outcomes, and baseline covariates are available from a randomized trial, but only individual‐level data on baseline covariates are available from the target population of nonparticipants.…”
Section: Introductionmentioning
confidence: 99%
“…The proof of approach 5 is closely related to that for approach 4. Westreich et al [27] provide a full proof in the appendix.…”
Section: A Appendixmentioning
confidence: 99%